2018
DOI: 10.1155/2018/2458281
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Andrographis paniculata on Platelet Activity in Healthy Thai Volunteers

Abstract: Background. Andrographis paniculata (AP) has been used in Thai traditional medicine to treat various infections, including the common cold and fever. Its bioactive compound, andrographolide, has shown antiplatelet activities in an in vitro study model. Since clinical studies of the effects of AP on the human platelet function have never been reported, we investigated its effect on platelet activity in ten healthy volunteers. Methods. Two grams of AP was taken 3 times within one day. The blood was withdrawn by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Clinically, it is applied in the treatment of diseases including respiratory tract infections, gastroenteritis, cold, fever 19 , and hypertension. Modern pharmacological studies show that Chuan Xinlian harbors anti-bacterial, anti-tumor 20 , cardiovascular protection 21 , hypoglycemic 22 , platelet aggregation inhibition 23 , liver protection 24 , among other effects with the anti-inflammatory effect being the most prominent 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it is applied in the treatment of diseases including respiratory tract infections, gastroenteritis, cold, fever 19 , and hypertension. Modern pharmacological studies show that Chuan Xinlian harbors anti-bacterial, anti-tumor 20 , cardiovascular protection 21 , hypoglycemic 22 , platelet aggregation inhibition 23 , liver protection 24 , among other effects with the anti-inflammatory effect being the most prominent 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation pattern observed in the 40 participants of this study before treatment is similar to one observed previously in healthy subjects and is known as hyperaggregation. 13,14 According to Thai traditional medicine theory, which supports these findings, the participants' Earth iCDR is the heaviest, slowestchanging element. Due to these reasons, no disaggregation pattern was observed.…”
Section: Discussionmentioning
confidence: 71%
“…However, as mentioned above, some other researchers only found that it had an inhibitory trend on platelet aggregation in patients, but did not find any changes in COX mRNA expression and arachidonic acid metabolites that caused this effect (Sirikarin et al. 2018 ). Therefore, it is necessary to systematically review the role of its compounds in haemostatic system.…”
Section: Discussionmentioning
confidence: 97%
“…Although, in recent years, AP has been reported to inhibit platelet aggregation potentially, it has not been observed to affect the mRNA expression of COX or the production of TXB 2 and P-selectin in clinical study (Sirikarin et al. 2018 ). In conclusion, a clear consensus on the specific mechanism underlying these phenomena is currently unavailable.…”
Section: Introductionmentioning
confidence: 99%